PENYULUHAN HUKUM TENTANG SISTEM INFORMASI TRANSAKSI JUAL BELI TANAH YANG TIDAK TRANSPARAN YANG DILAKUKAN MASYARAKAT ADAT SIMALUNGUN DI NAGORI DOLOK - Saragih, Dikki Saputra (Penerbit Widina, Widina Media Utama, 2024)
The community service activities carried out aim to provide legal education regarding the information system for non-transparent land sale and purchase transactions carried out by the Simalungun Indigenous Community in Nagori Dolok. The problem faced is that most of the participants still do not really understand legal responsibilities in the land buying and selling transaction information system. In terms of legal liability in the information system for land buying and selling transactions, there are still many people who are not responsible for civil actions against other people, which has resulted in the number of victims increasing so that many people feel that they have suffered a lot of losses related to the non-transparent processing of land buying and selling transactions. As a result of this activity, participants can know and understand the legal responsibilities of a good and correct land buying and selling transaction information system. Increased legal awareness and legal understanding of participants in understanding the importance of land ownership rights and the importance of legal accountability for an open land sale and purchase transaction information system so that they are aware of their actions.ABSTRAKKegiatan pengabdian masyarakat yang dilaksanakan bertujuan untuk memberikan Penyuluhan Hukum Tentang Sistem Informasi Transaksi Jual Beli Tanah Yang Tidak Transparan Yang Dilakukan Masyarakat Adat Simalungun Di Nagori Dolok. Permasalahan yang dihadapi adalah dimana para peserta sebagian besar masih sangat belum memahami pertanggungjawaban hukum dalam sistem informasi transaksi jual beli tanah. Dalam hal pertanggungjawaban hukum dalam sistem informasi transaksi jual beli tanah masih banyaknya tidak bertanggungjawab dalam hal perbuatan perdata kepada orang lain yang dimana mengakibatkan banyaknya para korban semakin bertambah sehingga banyak masyarakat yang merasa dirugikan banyak sekali terkait dalam pengurusan transaksi jual beli tanah yang tidak transparan. Hasil dari kegiatan ini, peserta dapat mengetahui dan memahami pertanggungjawaban hukum sistem informasi transaksi jual beli tanah yang baik dan benar. Meningkatnya kesadaran hukum dan pemahaman hukum peserta dalam memahami pentingnya hak milik atas tanah dan pentingya pertanggungjawaban hukum system informasi transaksi jual beli tanah yang terbuka supaya sadar dalam hal perbuatan.